2021
DOI: 10.1097/rhu.0000000000001787
|View full text |Cite
|
Sign up to set email alerts
|

IgG4-Related Disease

Abstract: Background:The tendency of IgG4-related disease (IgG4-RD) to form pseudotumors, as well as its multisystemic nature, makes it the perfect mimicker of many conditions. Moreover, some clinical, serological, radiological, or histological features of the disease might be shared with some mimickers.Recently, 4 clinical phenotypes have been identified, and patients grouped in each phenotype have distinctive demographic, clinical, and serological features and outcomes, and, as expected, for each phenotype, a set of d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 68 publications
0
15
0
3
Order By: Relevance
“…For differential diagnosis, the literature 7,8 showed that mimickers of IgG4-RD were mainly malignancy, vasculitis, Sjögren's syndrome, sarcoidosis, multicentric Castleman's disease, and infections.…”
Section: Discussionmentioning
confidence: 99%
“…For differential diagnosis, the literature 7,8 showed that mimickers of IgG4-RD were mainly malignancy, vasculitis, Sjögren's syndrome, sarcoidosis, multicentric Castleman's disease, and infections.…”
Section: Discussionmentioning
confidence: 99%
“…Misdiagnosis may be due to the fact that iMCD patients may have an elevated serum IgG4 level, while some cases of IgG4-RD may show Castleman-like histopathology. Besides, both conditions present with systemic lymphadenopathy with extranodal involvement, and affected organs may overlap between the two conditions [ 2 , 71 ].…”
Section: Inflammatory Conditions That Resemble Clinical or Histopatho...mentioning
confidence: 99%
“…In general, patients with IgG4-RD tend to be older than patients with iMCD [ 2 ]. Clinically, findings suggestive of iMCD are the presence of fever, high CRP, IL-6 and IgA levels and the absence of orbital, salivary gland and pancreatic involvement [ 71 ]. Atopic manifestations history is observed in almost 70% of the IgG4-RD cases but in <30% of patients with iMCD [ 66 ].…”
Section: Inflammatory Conditions That Resemble Clinical or Histopatho...mentioning
confidence: 99%
“…Despite the presence of heightened level of IgG4-positive plasma cells in the mucous membrane of the intestine during inflammatory bowel disease, this disease is not a condition of IgG4-related disease. The conditions of IBDs have no storiform fibrosis and phlebitis in their histological and clinical features, and therefore do not correspond to the profile of IgG4-related disease (Tanaka et al, 2018;Satou et al, 2020;Martín-Nares et al, 2022).…”
Section: Introductionmentioning
confidence: 99%